THE USE OF WORDLIST PLUS PICTURE TO INCREASE STUDENTS’ STOCK OF VOCABULARY - Christin I. M. Pangaila; Meity Muntuuntu; Paula Rombepajung (Fakultas Bahasa dan Seni, Universitas Negeri Manado, 2021)
This research aimed to see the effectiveness of using Wordlist plus picture in increasing students’ stock of vocabulary at the seventh grade of SMP Negeri 2 Tenga. This research used pre- experimental designed with one group pre-test and post-test. The result of this research found that Wordlist plus picture was effective in increasing students’ stock of vocabulary. The result showed that post-test was higher than pre-test. The mean score of pre-test was 5.00 and the mean score of post-test is 7.25 which means that the result of the post-test is higher than the pre-test. It can be stated that the students’ stock of vocabulary at the seventh grade of SMP N 2 Tenga is high in the post-test. So, it means Wordlist plus picture is effective in increasing students’ stock ofvocabulary at the seventh grade of SMP N 2 Tenga.